METHODOLOGY FOR USING MULTIMEDIA APPLICATIONS IN TEACHING ENGLISH TO PUPILS OF PRESCHOOL EDUCATIONAL ORGANIZATION (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The article outlines a pedagogical methodology for the intentional and developmentally appropriate integration of multimedia applications in teaching English to preschool pupils. The core focus is on aligning digital tools with the developmental needs of young learners to optimize language acquisition.